Preliminary Analysis on Muslim-Jewish Discourse in Medieval Period: The Case of al-Ghazali (d. 1111) and Maimonides (d. 1204) - Senin, Nurhanisah; Mohd Khambali @ Hambali, Khadijah; Wan Ramli, Wan Adli (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
This paper attempts to examine the Muslim-Jewish discourse in the medieval period. It discusses the intertwining discourses between Muslim-Jewish theologians and philosophers which emerged through their endeavors in elucidating the concept of God. This takes place further when the writings of the Mu‘tazilites indirectly influenced the Karaites of the Jewish sects through the Arabic writings that were commonly shared by the Muslims and the Jewish scholars. This can be observed as well in the case of al-Ghazali and Maimonides who were both prominent scholars in their respective religions. Although they did not chance upon each other and employ different methods of arguments, their writings however correspond which al-Ghazali’s influence can be seen in Maimonides’ writing. Hence, it can be summed that the Arabic medieval period as well as the concept of monotheistic belief which was the fundamental of Muslims and Jewish were the two factors that bind the Muslim and Jewish discourses in particular al-Ghazali and Maimonides.